Correlação entre parâmetros térmicos e estruturais na solidificação transitória de ligas hipomonotéticas do sistema Al-Bi-Cu - Moura, Danusa Araújo de (2020)
Aluminum alloys have significant application potential as a material for plain bearings due to their characteristics, mainly their low weight and the possibility of compositions with elements of lubricating properties dispersed in their matrix. According to studies carried out on binary alloys (Al-Bi, Al-Pb and Al-In), the values obtained for mechanical strengths are low, thus, the addition of a third alloy element is seen as positive in order to increase the load bearing capacity of these materials. Copper (Cu) is appointed as an alloying element that can be added to Al-Bi alloys in order to improve the mechanical behavior of these alloys and also provide gains in tribological properties. There are few studies that relate the thermal parameters with the microstructure/ morphology in ternary alloys, mainly under transient conditions of heat extraction. The present study aims to contribute to the development of correlation between thermal and structural parameters of the hypomonotetic alloys of the Al-Bi-Cu system (Al-2%Bi-3%Cu and Al-2%Bi-5%Cu). For the development of the present study, a descending vertical unidirectional solidification device was used. The thermal parameters such as solidification speed, cooling rate and thermal gradient were determined experimentally by cooling curves acquired along the length of the ingot and, then, correlated with the microstructural parameters: interphasic and secondary dendritic spacing as well as the diameter of the particles of bismuth. From the results obtained, it is observed that the presence of copper promotes the formation of a dendritic microstructure and that the secondary dendritic spacing, the interphase spacing and the diameter of the bismuth particles increase as a function of the increase in the relative metal / refrigerated position, which can be justified by the variation of both the cooling rate and the thermal gradient.